ISLAM DAN TRADISI LOKAL: KAJIAN TENTANG NILAI-NILAI DAKWAH DALAM TRADISI REBO WEKASAN DI DESA SUCI MANYAR GRESIK - Ali Sodikin (MIYAH : Jurnal Studi Islam, 2022)
Abstract: Da'wah is an activity that is carried out consciously in order to convey Islamic religious messages to others so that they accept the teachings of Islam and carry it out well in individual and social life to achieve human happiness both in the world and in the hereafter, using the media and certain ways. Culture tends to be followed by the supporting community from generation to generation from generation to generation, although it often happens that members of the community come and go due to the emergence of various factors, such as death and birth. Considering the function of culture is as a reference in behaving and behaving in society, every ethnic group will definitely develop values ??which are then used as a reference for interacting with others in order to create a society that maintains harmony and good friendship. From the data analysis, it was concluded that many da'wah values ??and Islamic elements were found in this local tradition. In this case, it includes several values ??that contain elements of da'wah, namely: mutual cooperation, religious values, educational values ??in culture, brotherhood values, and harmony in society. Kata kunci: Da'wah, culture and society